Identificación de los factores psicosociales en el consumo de alcohol en adolescentes de 15 a 17 años de la ciudad de Loja. - Mansanillas Rojas, Tatiana Cecibel (2015)
The present study of quantitative approach with descriptive scope has as aim identify some of the factors psicosociales (age of beginning of consumption, type of educational establishment, kind and factors partner - relative) in the consumption of alcohol of the teenagers from 15 to 17 years of Loja's city. The sample was shaped by 649 students belonging to firstly, the second and third year of baccalaureate of the educational fiscal institutions, fiscomisionales and particular. For this study the Questionnaire was in use for Teenagers: Aspects Psicosociales related to the consumption of alcohol. The results indicate that the age of beginning of consumption of alcohol is given in a range from 14 to 15 years in the different types of educational establishment; one thought that the masculine sex presents major use of alcohol and that they live through great part of the teenagers with his progenitors, and these have an academic top level and work 8 hours; one found that the holidays of relatives or friends it is the most frequent place of consumption and the equal ones are the most common accompanists for the ingestion of alcohol. .